Data-Centric Business and Applications Evolvements in Business Information Processing and Management-Volume 1 - Kryvinska, Natalia; Greguš, Michal (Lecture Notes on Data Engineering and Communications Technologies, 2019)
This book discusses processes and procedures in information/data processing and management. The global market is becoming more and more complex with an increased availability of data and information, and as a result doing business with information is becoming more popular, with a significant impact on modern society immensely. This means that there is a growing need for a common understanding of how to create, access, use and manage business information. As such this book explores different aspects of data and information processing, including information generation, representation, structuring, organization, storage, retrieval, navigation, human factors in information systems, and the use of information. It also analyzes the challenges and opportunities of doing business with information, and presents various perspectives on business information managing.